2019
DOI: 10.2196/10271
|View full text |Cite
|
Sign up to set email alerts
|

Appropriation of Mobile Health for Diabetes Self-Management: Lessons From Two Qualitative Studies

Abstract: Background To achieve clarity on mobile health’s (mHealth’s) potential in the diabetes context, it is necessary to understand potential users’ needs and expectations, as well as the factors determining their mHealth use. Recently, a few studies have examined the user perspective in the mHealth context, but their explanatory value is constrained because of their limitation to adoption factors. Objective This paper uses the mobile phone appropriation model to examine how … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 59 publications
1
26
1
2
Order By: Relevance
“…Since maintenance or achievement of health plays a major role, these users don’t need to be made aware of the relevance of a healthy lifestyle but might profit from recommendations by doctors or peers for suitable and easy-to-use apps. As Rossmann et al [ 34 ] showed in their study with diabetic patients, recommendations by doctors can be an important driver of app use. In turn, this user type will be a useful multiplier to communicate good experiences with an app to others, since interpersonal communication about the app in addition to normative and symbolic evaluations, especially the use of a cutting-edge nutrition app, are strong predictors of this appropriation pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since maintenance or achievement of health plays a major role, these users don’t need to be made aware of the relevance of a healthy lifestyle but might profit from recommendations by doctors or peers for suitable and easy-to-use apps. As Rossmann et al [ 34 ] showed in their study with diabetic patients, recommendations by doctors can be an important driver of app use. In turn, this user type will be a useful multiplier to communicate good experiences with an app to others, since interpersonal communication about the app in addition to normative and symbolic evaluations, especially the use of a cutting-edge nutrition app, are strong predictors of this appropriation pattern.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the MPA model has not only been applied to study the appropriation process of the innovation bundle mobile phone in total but in its basic principles and accordingly adapted forms also to study further areas and mobile applications, such as the mobile web [ 31 ], mobile Facebook use [ 32 ], or the relationship between mobile phone appropriation and migrant acculturation [ 33 ]. In the health domain, the model has already been applied to the study of diabetes apps and has unveiled their specific appropriation patterns [ 34 ]. Hence, as suggested by Wirth et al [ 25 ], our first research question is:…”
Section: Introductionmentioning
confidence: 99%
“…Related literature beyond text messaging programs about mobile apps reveals findings that are similar to ours. Patients have strong preferences for diabetes apps that are easy and efficient to use [43,44], and strong integration in patients' daily routines has also been noted as desired features of mobile apps [45,46]. Similarly, communication preferences themselves have been thought to be highly individual [47].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…This consideration of what is "data", reflects previous methods used in framework synthesis. 26,27 In the studies including participants with both Type 1 and 2 Diabetes, 15,28,29 only data pertaining to participants with Type 2 Diabetes was included in the analysis. In addition, using the software program Microsoft® Excel®, MON and MD independently extracted pertinent information about each study's characteristics, i.e.…”
Section: Data Extractionmentioning
confidence: 99%
“…14 The scoping review revealed an increased recent interest in exploring people's use of mHealth apps through qualitative approaches. 15,16,17 Qualitative approaches provide rich data on consumers' experiences which can inform app innovation. 18 In this context, the aim of this qualitative evidence synthesis was to identify and synthesise qualitative research relating to experiences of using mobile health (mHealth) applications to aid selfmanagement of Type 2 Diabetes.…”
Section: Introductionmentioning
confidence: 99%